A mixed-methods study of Bambara farming in Mtwara, Tanzania - Basile Boulay (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2017)
Economic research tends to focus on a reduced set of crops, leaving a vast array of crops under-researched. However, these 'marginal crops' have typically been farmed for centuries and are better suited for the local environment in which they are grown than crops prioritized within existing research. As such, they can contribute towards a less intensive and productivist mode of farming and help achieving important sustainable development goals. Our mixed-methods study conducted in Tanzania contributes to advancing knowledge of one such marginal crop, the Bambara nut. On the quantitative side, we surveyed 270 farmers across 32 villages in the Mtwara rural district to gather socio-economic and agricultural data. On the qualitative side, we ran focus groups in four villages to enquire about village norms and constraints surrounding the farming of Bambara. We show that Bambara is often seen as a vital crop for food consumption and food security, as it is easy to grow and has a strong nutritional content. However, despite selling at a high price, its market is not well developed due to lack of availability of improved seeds and unreliable marketing channels. We argue that developing the economic potential of indigenous crops constitutes a path towards greater agricultural sustainability as these crops are suited to local environments, need little chemical inputs, are drought resilient and extremely nutritious. Doing so would constitute a first step towards changing the existing and highly problematic agricultural paradigm and reducing farmers' dependency on input and output markets.
Keywords: O13; Q01; Q12; Q18; Q19; 330; agriculture; underutilised crops; mixed-methods; sustainability